The history and foundations of medical research ethics - Lenk, Christian (Henry Stewart Talks, 2022)
Germany: medicine in national socialism, The Nuremberg “doctors’ trial”, Research in humans: The Nuremberg Code of 1947, Invention of the Polio vaccine, The Tuskegee Syphilis study, Elements of consent, Medical research with human subjects: Declaration of Helsinki (1964-2013), Research with vulnerable groups